The value of large trees and their protection where elephants and trees co-exist - Cook, Robin Michael (University of the Witwatersrand, Johannesburg, 2024)
Increasing African elephant (Loxodonta africana) numbers in many southern African protected areas have raised concerns about their impact on large tree species and subsequent effects on biodiversity. However, sustainable strategies for managing elephant impact on particular large trees of concern require stakeholder support. Concerned stakeholders in South Africa's Associated Private Nature Reserves (APNR), a protected area containing a high density of waterholes and elephants, are implementing tree protection methods to protect large trees from elephant impact, but few studies have assessed these methods’ efficacy. This thesis aimed to understand stakeholder perception of the value of large trees. Thereafter, I investigate elephant impact on the large tree component within the APNR over a 12-year period while also assessing the relationship between the persistence of the nests of large tree nesting birds and that of the trees themselves. Lastly, I assessed the effectiveness of various implemented tree protection methods to mitigate against elephant impact. A combination of qualitative and quantitative analysis was used to measure stakeholders’ values on large tree and elephant population dynamics, as well as management strategies to reduce the impact on large trees. The results show that stakeholders were concerned about the loss of large trees and its impact on other species. However, they disagreed on the most effective management strategy to minimise elephant impact, with varying values across stakeholder generations and professions. The persistence trends of 2,758 large trees comprising three species of concern were analysed between 2008-2020 to understand the impact of elephants and other environmental factors on tree mortality. The annual large tree mortality rate from 2008-2020 was 5.6%, with varying declines among tree species and the most significant declines occurring during dry periods. Furthermore, the long-term impact of elephants on trees nested in by the critically endangered white-backed vulture (WbV, Gyps africanus) was studied in riparian and woodland habitats to investigate both tree and nest persistence. Ten tree species were utilised for nesting sites, with woodland trees more at risk to elephant impact verses those in the riparian habitat. However, there was no direct correlation between WbV nest loss and tree fall. Lastly, when considering tree protection methods, about half of the 2,758 trees surveyed were wire-netted as potential elephant impact mitigation strategy. Trees with a stem diameter >40 cm that were wire-netted had the highest persistence rates, but the wire-netting needed replacing after four years. Overall, wire-netting was the most practical method for larger- scale implementation, particularly on larger trees elephants cannot push over. Of the four tree protection methods evaluated in this study in terms of their effectiveness and practicality as a mitigation strategy, beehives were found to be the most effective at protecting trees but proved to be the most expensive in comparison to wire-netting, concrete pyramids and creosote jars
A Thesis submitted to the Faculty of Science Submitted in fulfillment of the requirements for the degree Doctor of Philosophy in Animal, Plant and Environmental Sciences in the Faculty of Science, University of the Witwatersrand, Johannesburg, South Africa, 2024
Keywords: Elephant impact; Elephant management strategies; Large trees; Stakeholders; Tree protection methods; Tree mortality; Wire-netting; SDG-15: Life on land